Effectiveness Of Law Enforcement Implementation In Case Of Middle Assistance Oriented On Restorative Justice - Moh. Suharto; Umar Ma'ruf (Law Development Journal, 2021)
The purpose of this study was to determine the implementation of a restorative justice system in cases of mild persecution in the community which has not been effective at this time. The method used in this approach is sociological juridical. Restorative justice is an alternative settlement of criminal cases which in the criminal justice procedure mechanism focuses on punishment which is converted into a dialogue and mediation process that involves the perpetrator, victim, family of the perpetrator/victim, and other related parties to jointly create an agreement on the settlement of a criminal case that is fair and balanced for both the victim and the perpetrator by prioritizing restoration to its original state and restoring the pattern of good relations in society Case LP/B/06/II/2018/Central Java/Res. Pbg/Sec. fret, The victim was subjected to physical violence by the suspect. Based on the report, the Mrebet Police Chief processed and completed the investigation file. The police chief through his authority directs to the victim that the case can be resolved by restorative justice. Even though he had refused, the victim finally agreed to make peace with the suspect. This also happened in the Grobogan area, where Ulil as the persecutor and Surip who was the persecuted party were facilitated by the police to make peace through restorative justice. However, not all of the community, especially victims of mild persecution, are willing to carry out legal settlements in restorative justice, where Ulil as the persecutor and Surip who is the persecuted party are facilitated by the police to make peace through restorative justice. However, not all of the community, especially victims of mild persecution, are willing to carry out legal settlements in restorative justice.